2012
DOI: 10.5713/ajas.2011.11287
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Effect of Melanin Influencing Factors on In vitro Melanogenesis in Muzzle Melanocytes of Differently Colored Hanwoo

Abstract: The present study was designed to investigate the effect of α-melanocyte-stimulating hormone (α-MSH), nitric oxide (NO) and L-cysteine on melanin production and expression of related genes MC1R, Tyr, Tyrp-1 and Tyrp-2 in muzzle melanocytes of differently colored three native Hanwoo cattle. Muzzle samples were taken from black, brindle and brown Hanwoo and purified melanocytes were cultured with α-MSH, nitric oxide and L-cysteine at 100 nM, 50 µM and 0.07 mg/ml of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Both α-MSH and NO in melanocytes promote melanogenesis by increasing tyrosinase activity [ 60 ]. In addition, Yang et al suggested that targeting NO signaling may be therapeutic and preventive because melanoma cells are characterized by high expression of NO synthase, and NO is deeply involved in increasing invasion and proliferation of melanoma cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both α-MSH and NO in melanocytes promote melanogenesis by increasing tyrosinase activity [ 60 ]. In addition, Yang et al suggested that targeting NO signaling may be therapeutic and preventive because melanoma cells are characterized by high expression of NO synthase, and NO is deeply involved in increasing invasion and proliferation of melanoma cells [ 61 ].…”
Section: Discussionmentioning
confidence: 99%